Genetic and phenotypic analysis of Tunisian Theileria annulata clones - Taylor, L.H.; Katzer, F.; Shiels, B.R.; Welburn, S.C. (Cambridge University Press, 2003)
Many parasite species are known to show high levels of genetic diversity, yet the consequences of this diversity for host-parasite interactions are not well understood. Variation in phenotypic traits such as growth rates and the ability to form transmission stages are raw material for natural and artificial selection to act upon with consequences for the evolution of the parasite species and disease control. In order to study genetic and phenotypic diversity amongst Theileria annulata parasites, a collection of 52 parasite clones was generated from cattle isolates and tick material recently collected in Tunisia. Genetic diversity was assessed using PCR-RFLP and monoclonal antibody markers, and genetically distinct clones selected for further study. Clones varied significantly in their growth rates in culture at 37 degreesC, their viability after a period of culture at 41 degreesC and their differentiation rates into transmission stages after culturing at 41 degreesC. The viability of a clone after culturing at 41 degreesC could not be predicted from its growth rate at 37 degreesC, but across clones, differentiation rates were positively correlated with growth rates at 37 degreesC. All 3 in vitro measures are likely to have relevance to parasite-host interactions in animals with clinical theileriosis, and should be acted on by within-host and between-host selection.